(untitled) (Configurazioni. Research on contemporary poetry, 2023)
The article traces and analyzes from a perspective at once critical and stylistic one of the intellectual debates that occurred at the historical threshold of 1993, identified as the watershed date of a «crisis of criticism», and the positions they communicate regarding anthological theory and practice. Its protagonists are Giovanni Raboni and Alfonso Berardinelli: the object of contention (or its pretext) is Per la poesia di Giorgio Manacorda (Editori Riuniti, 1993), a «panoramic, anthological and theoretical pamphlet». The stages of this querelle on the subject of the poetic anthology are marked by some interventions that appeared in l’Unità and Corriere della sera between May 24 and June 7, 1993.